PENGARUH KEGIATAN EKSTRAKURIKULER SENI TARI DI SD AL CHOIR PANGERAN JAYAKARTA TERHADAP PENDIDIKAN KARAKTER SISWA - Hanalisahara Rachmanto; Endang Wahyudiana; Tunjungsari Sekaringtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of dance extracurricular activities on character education of students at Al Choir Pangeran Jayakarta Elementary School, focusing on four character indicators: discipline, responsibility, cooperation, and self-confidence. Using a quantitative approach with a quasi-experimental method and a pretest-posttest control group design, the sample consisted of 30 second-grade students divided into an experimental group and a control group. The research instrument was a Likert scale questionnaire, and the data were analyzed through normality, homogeneity, paired sample t-test, and independent sample t-test tests. The results showed a significant increase in the character of students in the experimental group after participating in dance activities, as well as a significant difference in posttest scores compared to the control group. Thus, dance extracurricular activities have been proven to have a positive effect on the formation of character education of elementary school students.